Determining Student's Welding Skill for Visual Welding Inspector (CSWIP 3.0) Certificate Using Profile Matching - Friendly; Berti Sari Br. Sembiring; Zakaria Sembiring; Piktor Tarigan; Rezha Destiadi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Welding is skill needed in many machinery and factory industries. Welding as skill is acknowledged by having a certificate. As certification cost is high, the skill must match the criteria for each test in a certification. In recent years, Politeknik Negeri Medan has held 7 times Visual Welding Inspector (CSWIP 3.0) certification with 57% of the participant pass the certification. Many participants not sure about the possibility of passing the certification process thus hesitating in taking this exam for the certification is costly. This research purpose the usage of profile matching method in determining the possibility of passing the certification. The result is suggested as a recommendation for taking the exam, but not preventing the examinee to take the certification test. The result shown that according to profile matching criteria, 75% people with recommendation is passing the certification, while all the people who didn’t meet the criteria and still taking the exam didn’t pass the test for certification.